Low computational cost method to calculate the hosting capacity in radial low voltage networks - Morales-Conde, Juan; Martín-Rivas, Sebastián; Pérez-Ruiz, Juan (My University, 2019)
This study presents a low computational cost method to compute the hosting capacity of each user in a radial single phase power network. It is assumed every user install generation. The method is based on two key points, one is the Thevenin equivalent for the installation of each user and for the whole system, the other is the representation of the operation region through the contour of the regions for the Thevenin circuits parameters. The method calculates the range of power injection allowed for each user in order to comply with the network and devices constraints. This range can be included in optimization problems to define the feasible operation region avoiding the explicit inclusion of the power flow equations. The method is illustrated on a simple case study with three users.
Keywords: Energía eléctrica - Distribución; Domestic PV; Radial network; Feasible region operation; Thevenin equivalent circuit; Network constraints